Describing hypoglycemia - definition or operational threshold? - Rozance, Paul J. (2010)
Severe glucose deficiency leads to cerebral energy failure, impaired cardiac performance, muscle weakness, glycogen depletion, and diminished glucose production. Thus, maintenance of glucose delivery to all organs is an essential physiological function. Normal term infants have sufficient alternate energy stores and capacity for glucose production from glycogenolysis and gluconeogenesis to ensure normal glucose metabolism during the transition to extrauterine life and early neonatal period. Milk feedings particularly enhance glucose homeostasis. Energy sources often are low in preterm and growth restricted infants, who are especially vulnerable to glucose deficiency. Plasma glucose concentration is the only practical measure of glucose sufficiency, but by itself is a very limited guide. Key to preventing complications from glucose deficiency is to identify infants at risk, promote early and frequent feedings, normalize glucose homeostasis, measure glucose concentrations early and frequently in infants at risk, and treat promptly when glucose deficiency is marked and symptomatic.